The Effect of Predict Observe Explaint (POE) Learning Model on Competency Process Standards - Dian Eka Nugraheni; Subuh Anggoro (UM Purwokerto Press, 2025)
In the process of learning the underlying mathematical concepts in students, it is often the case that the process stabdards of students mathematical competence have not been completed. Mathematics has a standard mathematical process, namely problem solving, reasoning, communication, connection, and representation. This type of research is a quasi experimental research using posttest only control design which aims to determine whether there is an effect of the Predict Observe Explaint (POE) learning model on the standard process of mathematics competence of grade V students of MIM Petambakan, Banjarnegara. Hypothesis testing in this study used a t-test which was preceded by a normality test using the kolmogrov-smirnov test and homogeneity test using Levene’s test. The test was conducted using SPSS 22 with a significance level of 5%. Based on the results of statistical analysis, it is obtained that there is a positive and insignificant influence between the Predict Observe Explaint (POE) learning model on the standard process of mathematics competence in class V MIM Petambakan with a sig value of 0.923>0.05 and beta standard coefficient 0.919.